Optimization of photocatalytic degradation of sulfamethoxazole from wastewater using developed N-doped TiO2/biochar - Hailu Ashebir; Saeideh Babaee; Palesa Diale; Abebe Worku; T.A.M. Msagati; Jemal Fito Nure (Results in Engineering)
This study introduces a novel N-doped TiO2/biochar nanocomposite aimed at enhancing the photocatalytic degradation of the antibiotic sulfamethoxazole (SMZ) in pharmaceutical effluent. Utilizing Response Surface Methodology (RSM), key operational parameters were optimized, achieving SMZ's impressive removal efficiency of 98.3 % from synthetic, and 86.6 % from actual wastewater samples. Characterization via X-ray diffraction (XRD) showed a predominant anatase phase, Diffuse Reflectance Spectroscopy (DRS) indicated a bandgap of 2.56 eV, and Fourier Transform Infrared Spectroscopy (FTIR) confirmed nitrogen doping. The optimization involved an agitation period of 95 min, a dosage of 1.5 g/L, a pH of approximately 5, and an SMZ concentration of 110 mg/L. RSM employed Central Composite Design (CCD) comprising four variables and 30 experimental runs to model and analyze degradation process. The quadratic model from RSM exhibited strong statistical significance (p < 0.0001) with an R² value of 0.9998 and a non-significant lack of fit (p = 0.3014), thereby confirming its validity. A close alignment with the pseudo-first-order reaction model was evidenced by a rate constant (kapp) of 0.0208 and an R² value of 0.991, consistent with the assumptions of the Langmuir-Hinshelwood model. Notably, this study successfully developed a highly durable nanocomposite (sustaining >6 cycles with <5 % efficiency loss), and displayed 1.58 times greater activity under visible light compared to pristine TiO2 and effectively degraded 95 % of pharmaceutical residues within just 30 min, significantly surpassing the 64.2 % degradation rate of bare BC. This demonstrates the nanocomposite's potential as a scalable and energy-efficient solution for wastewater treatment.